Socio-economic impact of air transport in small island states : an evaluation of liberalisation gains for the Caribbean Community (Caricom) - Warnock-Smith, David (Cranfield University, 2008)
As the primary output of the air transport sector, the flow of air passengers plays an important role in the economic and social welfare of nations, while the sector’s regulatory framework represents the main vehicle through which government can exert a given level of influence over the provision of such services. This research modifies and applies existing macroeconomic impact theory to the Caribbean Community (Caricom), before developing an improved method by which to evaluate the supply and demand effects of further air policy liberalisation in the region. It was found, using an original multi-method approach, that the Caricom air transport sector contributed on average 16.9% towards GDP and 14.2% of the labour force. A large variation around these regional averages were noted, however, and are said to be primarily determined by exogenous factors such as relative size of GDP, relative sector diversity and relative level of trade dependency, with the largest impacts being recorded in smaller, tourism dependent islands. A significantly different picture emerges if catalytic impacts are removed showing the strength of the multiplier, with contribution to GDP reducing to 2.8% and the percentage of the labour force declining to around 1.9%. Multipliers for Trinidad & Tobago (-0.40), the Bahamas (2.38) and Guyana (2.95) were below the global average, however, reiterating the heterogeneity of the sample and by extension the whole Caribbean community. Using fixed-effects panel regression, the removal of bilateral or multilateral entry and tariff barriers were found to increase the average country-pair’s arriving and departing passenger levels by 250,000, 22,000 and 8,000 on NA-, UK- and Intra-Caricom markets respectively, given a one unit increase in air policy liberalisation. The actual impact of liberalisation on any given market was moderated by unobserved fixedeffect dummy variables which provided each country-pair with a unique intercept value to take account of underlying network and market maturity differences. Hence, all currently restricted country-pairs in the sample would stand to gain around 183,000 passengers per annum if a gradual bilateral approach to liberalisation was adopted. A counterfactual analysis suggested that a one unit policy change in the year 2000 on all 13 currently restricted markets would have increased passengers levels to around 16.4 million. In the multilateral scenario both restricted and partially liberal markets experience simultaneous reform resulting in a predicted traffic increase of 621,000 passengers per annum. Using ‘within sample’ multipliers, the extra bilateral output is estimated to increase baseline expenditure by US$51 million or US$16 million per annum when catalytic spending is included and excluded respectively. With multilateral reform, an additional US$164 million or US$53 million would accrue to the regional economy. When compounded, the total time-series effect of multilateral liberalisation totals 3.7 million passengers on top of the baseline, boosting regional output by 2.6% or 0.7% and increasing employment by 1.4% or 0.2%. Given previous evidence, extra-regional reform will not take place multilaterally in the foreseeable future. In the short to medium term, a combination of a revised Caricom MASA and gradual moves towards bilateral liberalisation would produce optimum macroeconomic results. The historical and counterfactual findings of this research challenge current restrictive practises in the region. Further assistance with respect to foreign carrier entry and regional carrier integration could stimulate the desired fare, capacity, frequency and connectivity improvements and generate significant increases in overall welfare.